Distal outcomes of communal goal mismatch: a longitudinal study of underrepresented students in STEM - Bonilla, Ashley; Schultz, Wesley; Woodcock, Anna; Hernandez, Paul R. (Frontiers in Psychology, 2025)
Using the goal congruity framework, this longitudinal study investigated whether communal goal mismatch predicted distal outcomes of STEM intentions, STEM identity, and a sense of belonging among students pursuing degrees in STEM fields. We hypothesized that students who experienced a negative mismatch (i.e., perceived insufficient opportunities to fulfill communal goals) would show lower intentions to pursue a STEM career, would be less likely to express a STEM identity, and would be less likely to feel like they belonged in their STEM field 1 year later. Results showed that students reported lower intentions to pursue the STEM fields when their perceived communal goal affordances in STEM were insufficient. They were also less likely to have a strong STEM identity. However, a negative mismatch did not significantly predict a sense of belonging. Overall, the results highlight the role of goal affordances in students’ academic and career choices.